A System of Child Detection in Car Using Thermal Sensor - Norhuzaini, Ahmad Aminnuddin; Yaacob, Maslina; Ngajikin, Nor Hafizah (Journal of Sustainable Manufacturing in Transportation, 2022)
There are some cases about the child died in the car that causes by the parent did not aware their child being left in the car in long duration time. Therefore, there is a project that can overcome the problem of children being left behind in the car that is a prototype that can detect children in the car by using heat-sensing technology and effective indicators to users so that users are aware of the indicators in the prototype system be created. The system of the prototype consists of Arduino MKR WIFI 1010, thermal sensor, buzzer, LEDs, relay, and power bank that be constructed in circuit. This work evaluates the prototype able to detect child remain in car using thermal sensor with detection range is 37cm on the rear car seat and also able to notify the user about its using indicator LED and buzzer alarm. The prototype will connect to the car to operate as the flow in the flowchart. This prototype helps the user to prevent the child be left in a car.